SITE INDEX PREDICTION OF SMALLHOLDER PLANTATIONS OF KAYU BAWANG (Disoxylum mollissimum Blume) IN BENGKULU PROVINCE - Hengki Siahaan; Agus Sumadi (Indonesian Journal of Forestry Research, 2016)
Kayu bawang (Dysoxylum mollissimum Blume) has been planted almost in all districts of  Bengkulu Province, Indonesia, but yet no study has been conducted to analyze the site quality of  this species. This paper studies the site quality of  Dysoxylum mollissimum Blume of  smallholder plantations by establishing 32 permanent sample plots (PSPs) distributed in six districts of Bengkulu Province and measured periodically from 2006 to 2012. Site quality was determined by phytocentric method which used stand dominant height as a indicator. The result shows that the best model for dominant height growth of  Dysoxylum mollissimum Blume in Bengkulu Province was the Schumacher model expressed  by the equation: Ln Ho = (3.06 + ai) – 2.05/A (R2 = 96.5%, Absolute Mean Residual (AMRES) = 0.82 and Average Percentage Difference (APD) =5.03%). The relevant site equation for this species derived from the dominant height growth model was:  Ln Si = Ln H0 – 2.05 (1/12-1/A) for an index age of  12 years. Based on this equation, the sites were classified into 5 classes having an equal range of  3 m i.e. SI < 16 m; 16 m = SI < 19 m; 19 m = SI <  22 m; 22 m = SI < 25 m; and SI = 25 m: for site classes I, II, III, IV, and V representing from the lowest to the highest productivity respectively. Site class I, the poorest site, was found on the upland areas with an altitude of  > 850 m above sea level on andosol soil type. Adversely, the best site (site class V) was found at lowland areas with an altitude of  < 300 m above sea level and on ultisol soil type.